Pancreatic Stones in Children with Chronic Pancreatitis: A Case Report - Nuraini Irma Susanti; Nicodemus Nicodemus (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Chronic pancreatitis is a continuous progressive inflammation of the pancreas that can cause recurrent abdominal pain. The incidence of chronic pancreatitis in children is on an upward trend in recent years. The purpose of this case report is to enhance clinician's insight in considering chronic pancreatitis as a differential diagnosis in cases of recurrent abdominal pain in children. Case: We reported a case of chronic pancreatitis with pancreatic stones in a 12-year-old child. The patient came with complaints of recurrent upper left abdominal and heartburn accompanied by nausea and vomiting. Epigastric and left hypochondriac tenderness were found. Laboratory examination showed an increase in pancreatic enzymes up to 6x the normal value. The results of abdominal CT-scan and MRCP showed multiple pancreatic stones with pseudocysts. The patient then underwent the Puestow procedure. Postoperatively, the complaints of abdominal pain resolved and the pancreatic enzymes improved significantly. Discussion: The diagnosis of pancreatitis must meet 2 out of the 3 criteria that have been determined. Primary management includes fluids, analgesics, early nutrition, and surgery in cases of chronic pancreatitis accompanied by complications such as pseudocysts or pancreatic stones. Conclusion: This case teaches the need for a careful clinical approach and consideration of chronic pancreatitis as a differential diagnosis in a child with recurrent abdominal pain.